Wings: Come fly with us: A recruitment video for Wings Institue of Global Careers - Chua, Lynette Krystle T. (Animo Repository, 2011)
Wings is having challenges in communicating effectively to their target audience that training is advised to have a higher passing chance in the entrance test of commercial airline companies. According to Wings Institute of Global Career's research, there is only a 3% chance of passing the recruitment process without training, while students who went through training with Wings has 90% chance of passing the recruitment process. This recruitment video will capture the essence of the Flight Cabin Crew course, its role and nature through the different programs.